2010
DOI: 10.1186/1471-2458-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Household costs of illness during different phases of tuberculosis treatment in Central Asia: a patient survey in Tajikistan

Abstract: BackgroundIllness-related costs incurred by patients constitute a severe economic burden for households especially in low-income countries. High household costs of illness lead to impoverishment; they impair affordability and equitable access to health care and consequently hamper tuberculosis (TB) control. So far, no study has investigated patient costs of TB in the former Soviet Union.MethodsAll adult new pulmonary TB cases enrolled into the DOTS program in 12 study districts during the study period were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 23 publications
6
37
1
1
Order By: Relevance
“…In contrast, a Haitian study reported 75 DOT visits per patient [32]. Along the same lines, studies from Tanzania and Tajikistan mentioned fewer than 80 DOT visits per patient [11, 12]. Nonetheless, these differences in DOT visits might be associated with difference in treatment strategies (i.e., daily dose vs. twice-weekly dose, DOT at clinic vs. weekly packing of the daily dose) employed at these settings.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a Haitian study reported 75 DOT visits per patient [32]. Along the same lines, studies from Tanzania and Tajikistan mentioned fewer than 80 DOT visits per patient [11, 12]. Nonetheless, these differences in DOT visits might be associated with difference in treatment strategies (i.e., daily dose vs. twice-weekly dose, DOT at clinic vs. weekly packing of the daily dose) employed at these settings.…”
Section: Discussionmentioning
confidence: 99%
“…), characteristics of the household’s dwelling, water, sanitation and consumption of meat. While the 2005, 2007 and 2008 surveys collected the same asset variables, asset indicators were added to the 2011 survey based on the recent work of Ayé [12], allowing to account for change in households wealth related to economic growth (e.g. ownership of mobile phone).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, conducting interviews with tuberculosis (TB) patients in Tajikistan, Ayé et al collected information on medical and non-medical expenditures, as well as loss of income. Their study showed that the three largest shares of the direct costs of TB patients were special foods (29%), drugs (27%) and transport (25%), while medical fees expenditures represented only 7.3% of the direct costs [6]. The expenditures on drugs – legally free of charge for TB patients – concerned mainly additional, symptomatic treatment such as vitamin injections or intravenous rehydration, which are not essential drugs for TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycosides can produce significant side-effects, including irreversible ototoxicity, estimated to occur in 25–60% of patients treated for MDR-TB, depending on methods of measurement [2–5]. Even if surviving to cure, MDR-TB treatment itself is impoverishing [6], while ototoxicity further limits a patient’s ability to regain employment and may compound social isolation.…”
Section: To the Editormentioning
confidence: 99%